Conceptual Problem Solving and Student's Empirical Inductive Reasoning in Elasticity Subject - Mulyati, Restina Muji; Nugroho, Sunyoto Eko; Sulhadi, Sulhadi (Universitas Negeri Semarang, 2020)
Conceptual problem solving skills are one of the factors for student success in learning physics. Problem solving skills have a close relationship with reasoning skills. This study aims to analyze conceptual problem solving and student’s empirical inductive reasoning in learning physics in elasticity subject. This study used a quasi-experimental method with a one-shot case study research design. The research data were obtained from written tests. For conceptual problem solving skills, the average score percentage for principle aspects was 50.79%, justification aspects 3.17%, and plan aspects 38.49%. The results showed that the aspects of student justification in the elasticity subject were still low. Students have not been able to provide a complete explanation of why a principle or law of physics applies to a problem. For empirical inductive reasoning skills, the percentage score for the class inclusion pattern average was 31%, the conservation pattern was 10%, and the serial ordering pattern was 38%. Students have not been able to apply conservation thinking to an object, meaning that students do not understand that if nothing is added or removed from an object, then the properties or characteristics of the object will remain the same even though their appearance is different. The research results are expected to provide benefits, namely: (1) for students, as motivation to improve learning performance so that good learning outcomes are achieved, and (2) for teachers, as a basis for applying appropriate learning methods to develop student’s conceptual problem solving and empirical inductive reasoning skills.